Faktor-Faktor Yang Mempengaruhi Persepsi Petani Terhadap Budidaya Tanaman Hidroponik di Aceh Besar dan Banda Aceh - Khumaira Khumaira; Sri Fitri; Diah Eka Puspita (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The role of vegetables in everyday life is vital as a source of vitamins for family health as well as as a family source of income. But today the number of farmlands for vegetable cultivation is decreasing for a long time, due to the increasing number of buildings and housing being built. The objective of the research is to find out a picture of the use of hydroponic vegetables, the perception of farmers and to analyze the factors that influence farmers' perceptions of the innovation of hydroponic vegetables in the City of Banda Aceh and Greater Aceh. The number of respondents in this study is 10 respondents. Sampling technique is done by saturated sampling. (sampel sensus). Based on the results of the analysis it can be concluded that the real influential variables are business experience, distribution, purchasing power and innovation, whereas the real non-influential are age and education. Based on the F test, all variables have a real influence on farmers' perceptions of hydroponic vegetable cultivation tests